Ministry of Supply and Internal Trade Ministerial Decree No. 223 of the Year 2013 Issued on 9/6/2013 On Regulating the Packing and Trading Activities Related to the Pasta, Vegetable Oils and Margarine = وزارة التموين والتجارة الداخلية قرار وزراى رقم 223 لسنة 2013 صادر بتاريخ 9/7/2013 فى شأن تنظيم تعبئة وتجارة المكرونة والزيوت النباتية والمسلى الصناعى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.